1990
DOI: 10.1016/0014-5793(90)81404-c
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β induces synthesis and secretion of interleukin‐6 in human chondrocytes

Abstract: Increased concentrations of interleukin‐6 (IL‐6) have been found in the synovial fluid of patients with osteoarthritis, rheumatoid arthritis and crystal‐related joint deseases. It is therefore of great interest to identify the cells responsible for the production of IL‐6, and to investigate whether IL‐6 plays a role in the pathogenesisof degenerative or inflammatory joint diseases. Here we show that human interleukin‐1β (IL‐1β) induces IL‐6 synthesis and secretion in differentiated human chondrocytes. In organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…and tumor necrosis factor-␣ can also stimulate the production of IL-6 by articular cartilage chondrocytes (56,57). As previously reported by others (34, 55), we found that the effect of IL-6 requires the presence of its soluble receptor (sIL-6R) in the culture medium.…”
Section: Figsupporting
confidence: 69%
“…and tumor necrosis factor-␣ can also stimulate the production of IL-6 by articular cartilage chondrocytes (56,57). As previously reported by others (34, 55), we found that the effect of IL-6 requires the presence of its soluble receptor (sIL-6R) in the culture medium.…”
Section: Figsupporting
confidence: 69%
“…Furthermore, we (21) and others (22,23) found IL-1 to be a strong inducer of IL-6 synthesis and secretion in human chondrocytes. This observation raised the question of whether IL-6 may act on these cells in an autocrine manner.…”
supporting
confidence: 60%
“…Whereas Guerne et al (22) found that chondrocytes in monolayer culture without stimulation released 200 B9 units of IL-6 per milliliter of medium within 72 hours, several experiments with our agarose cultures yielded 3,200-50,000 B9 units of IL-6 per milliliter of medium in 72 hours. Also, in monolayer cultures, we recently found 3,100 B9 units of IL-6 per milliliter within 24 hours (21). From dose-response experiments in other systems, we know that 200 B9 units per milliliter of medium, as found by Guerne et a1 (22), is not sufficient for the stimulation of IL-6-responsive genes.…”
Section: Discussionmentioning
confidence: 84%
“…Cytokines that have been implicated in degenerative joint disease are interleukin-1 (Chang et al, 1986(Chang et al, , 1992Goldring et al, 1988;Verschure and Van, 1990;Davies et al, 1992), tumor necrosis factor (Campbell et al, 1990a,b;Pickvance et al, 1993), interleukin-6 (Bender et al, 1990), andinterleukin-8 (DeMarco et al, 1991;Elford and Cooper, 1991). Collectively, these cytokines increase fibrocartilage degradation by stimulating the synthesis of matrix-degrading enzymes by local cell populations.…”
Section: Temporomandibular Joint Diseasementioning
confidence: 99%